UPAYA MENINGKATKAN KEMAMPUAN PROBLEM SOLVING ANAK MELALUI PERMAINAN TRADISIONAL DAM-DAMAN - Ade Yeni; Husni; Ujang Endang (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
Early Childhood Education (PAUD) plays an essential role in preparing children’s physical and spiritual growth before entering primary education. It helps develop fundamental abilities, including social skills and problem-solving competence. However, observations at Kober Nurul Ihsan revealed several issues such as lack of concentration, hyperactivity, sleepiness, impatience, and haste in completing activities. These factors hinder children’s ability to follow instructions and think systematically. This study employed a quantitative experimental method conducted at Kober Nurul Ihsan Selamanik Cipaku, Ciamis Regency, involving 12 children as participants. Data were collected through observation sheets and analyzed quantitatively using SPSS. The results showed that the traditional game Dam-Daman effectively improved early childhood problem-solving abilities. Before treatment, the average score was 9.75 (Developing category), increasing to 21.75 after treatment, with a gain of 12 points. This improvement covered cognitive, social, and emotional aspects. The Dam-Daman game-based learning process enhanced children’s focus, patience, sportsmanship, and responsibility, proving it to be an enjoyable and meaningful learning medium for early childhood education.